Greater aggressiveness in the 2_A1 lineage of Phytophthora infestans may partially explain its rapid displacement of the US‐1 lineage in east Africa - Njoroge, A.W.; Andersson, B.; Yuen, J.; Forbes, G. (Wiley, 2018)
The displacement in east Africa of the US‐1 clonal lineage of Phytophthora infestans by 2_A1 clonal lineage has been very rapid. This study tested the hypothesis that dominance of 2_A1 could be due, at least in part, to the increased aggressiveness of 2_A1 over US‐1, using both a detached leaf assay (DLA) and a tuber slice assay. The assays were conducted in Uganda and Kenya but US‐1 was only assayed in Uganda, because isolates could not be moved across borders and no potato US‐1 isolates were available in Kenya. All isolates were collected from potato and compared on two potato cultivars (Kachpot‐1 and Sarpo Mira), with the 2_A1 isolates also tested on tomato cultivar Rio Grande. Additionally, a tuber slice assay was done to test whether the capacity to infect tubers differed between 2_A1 and US‐1. The aggressiveness of the isolates in the DLA varied significantly both within and among isolates classified according to clonal lineage and for type of host. The 2_A1 isolates were significantly more aggressive than US‐1 isolates on both potato varieties evaluated. There were no significant effects of clonal lineage or potato cultivar used in the tuber assay. No significant correlation between foliar and tuber pathogenicity was observed. The 2_A1 isolates were significantly more aggressive on potato than on tomato. An effect of location was also observed in the DLA, on both hosts. It can be concluded from this study that greater pathogenicity of 2_A1 is at least partly attributable to its increased aggressiveness on potato.